Continuing Education for Pregnant High School Students through Knowledge-Bridging using Self-Giving Modules - Tudy, Randy Ale; Millan, John (Jurnal Pendidikan Progresif, 2023)
Continuing Education for Pregnant High School Students through Knowledge-Bridging Using Self-Giving Modules (KBSM). Objectives: This action research aims to determine if the Knowledge-Bridging using Self-Giving Modules (KBSM) helps pregnant students continue schooling. Methods: This action research employed a phenomenological qualitative inquiry.  Using validated interview guide questionnaires, nine participants, composed of parenting students, advisers, guidance counselors, and administrators, participated in the Key Informant Interviews (KII). Data were analyzed using thematic analysis. Findings: Results showed ten identified pregnant students finished the school year. The participants affirmed the effectiveness of KBSM saying that the modules allowed them to continue their education and increased their determination to succeed. Moreover, the findings revealed two essential points. First, the KBSM was instrumental in protecting pregnant students. Second, there is a need to institutionalize the program because it just started as an initiative of a values subject teacher. Conclusion: Hence, the KBSM was able to help pregnant students continue their studies while handling pregnancy and taking care of their baby.  Keywords: education, teenage pregnancy, high school students, knowledge-bridging, action research, Philippines.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202305